The Importance Of The Extension Tool In Reducing The Inequality Of Yarn - Sanobar Atoevna Khamraeva; Nodira Bakhtiyarovna Yusupova; Dilmukhammad Davronbek Ogli Atambaev; Muhriddin Hakimjon Ogli Hasanov (The American Journal of Engineering and Technology, 2020)
In the spinning process, spinning machines have improved the stretching tool, reducing their unevenness by straightening and parallelism of fiber ends, reducing the number of yarn breaks in the production of quality textile and knitted fabrics, a sharp increase in labor productivity, reducing production costs, other economic indicators.